Chondrogenically primed tonsil-derived mesenchymal stem cells encapsulated in riboflavin-induced photocrosslinking collagen-hyaluronic acid hydrogel for meniscus tissue repairs. (15th April 2017) - Koh, Rachel H.; Jin, Yinji; Kang, Byung-Jae; Hwang, Nathaniel S.
Graphical abstract: Abstract: Current meniscus tissue repairing strategies involve partial or total meniscectomy, followed by allograft transplantation or synthetic material implantation. However, allografts and synthetic implants have major drawbacks such as the limited supply of grafts and lack of integration into host tissue, respectively. In this study, we investigated the effects of conditioned medium (CM) from meniscal fibrochondrocytes and TGF-β3 on tonsil-derived mesenchymal stem cells (T-MSCs) for meniscus tissue engineering. CM-expanded T-MSCs were encapsulated in riboflavin-induced photocrosslinked collagen-hyaluronic acid (COL-RF-HA) hydrogels and cultured in chondrogenic medium containing TGF-β3. In vitro results indicate that CM-expanded cells followed by TGF-β3 exposure stimulated the expression of fibrocartilage-related genes ( COL2, SOX9, ACAN, COL1 ) and production of extracellular matrix components. Histological assessment of in vitro and subcutaneously implanted in vivo constructs demonstrated that CM-expanded cells followed by TGF-β3 exposure resulted in highest cell proliferation, GAG accumulation, and collagen deposition. Furthermore, when implanted into meniscus defect model, CM treatment amplified the potential of TGF-β3 and induced complete regeneration. Statement of Significance: Conditioned medium derived from chondrocytes have been reported to effectively prime mesenchymal stem cells toward chondrogenic lineage. Type I collagen is the main component of meniscus extracellular matrix and hyaluronic acid is known to promote meniscus regeneration. In this manuscript, we investigated the effects of conditioned medium (CM) and transforming growth factor-β3 (TGF-β3) on tonsil-derived mesenchymal stem cells (T-MSCs) encapsulated in riboflavin-induced photocrosslinked collagen-hyaluronic acid (COL-RF-HA) hydrogel. We employed a novel source of conditioned medium, derived from meniscal fibrochondrocytes. Our in vitro and in vivo results collectively illustrate that CM-expanded cells followed by TGF-β3 exposure have the best potential for meniscus regeneration. This manuscript highlights a novel stem cell commitment strategy combined with biomaterials designs for meniscus regeneration.